2015
DOI: 10.4236/psych.2015.61007
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Negative Acts Questionnaire (NAQ) in a Sample of Greek Teachers

Abstract: Workplace bullying/mobbing is a globally recognized problem. In numerous studies executed in Europe and North America, workplace bulling/mobbing is associated with psychological, psychosomatic, and behavioral effects on the individual, while it causes severe side-effects on the professional environment. Negative Acts Questionnaire-Revised (NAQ-22) has been widely used by researchers to assess the phenomenon. The purpose of this study is to assess the psychometric properties of NAQ-22 in a sample of 265 primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 28 publications
5
17
1
4
Order By: Relevance
“…The findings suggest that in India, bullying at work is conceptualized more in terms of psychological violence rather than a form of physical violence. This corresponds to the view held by World Health Organization regarding nature of workplace bullying (as cited in Kakoulakis et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings suggest that in India, bullying at work is conceptualized more in terms of psychological violence rather than a form of physical violence. This corresponds to the view held by World Health Organization regarding nature of workplace bullying (as cited in Kakoulakis et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…NAQ-R is the most widely tested and extensively used indirect measure of workplace bullying (Giorgi, Arenas, & Leon-Perez, 2011;Kakoulakis et al, 2015) that has been used in more than 300 research projects (Notelaers & Einarsen, 2013) across different sectors with more than 50,000 respondents and over 40 countries worldwide. Although an internationally acclaimed indirect standardized measure of workplace bullying (Ciby & Raya, 2015), NAQ-R has been developed in Norway (Einarsen, Hoel, & Notelaers, 2009) and tested mostly in Western countries.…”
Section: Aim Of the Studymentioning
confidence: 99%
“…In their scale development article, Einarsen et al (2009) provide reliability evidence and evidence for the validity of the 22-item measure as an index of the frequency of being a bullying target. Further, two recent studies found evidence of reliability and construct validity in samples in Japan (Takaki et al, 2010), Korea (Nam, Kim, Kim, Koo, & Park, 2010), and Greece (Kakoulakis et al, 2015). For the present study, items were modified in such a manner as to assess the frequency of perpetrating acts of bullying (e.g., "In the past year, how often have you given a person tasks with unreasonable deadlines?").…”
Section: Bullyingmentioning
confidence: 99%
“…Este questionário mostra-se útil para investigar grandes amostras populacionais, sendo de fácil aplicação, e pode ser adaptado para culturas diversas (Einarsen, Hoel, & Notelaers, 2009;Maciel & Gonçalves, 2008). Os resultados em várias amostras evidenciaram que o instrumento possui alta consistência interna, tendo os pesquisadores encontrado Alpha entre 0,86 e 0,93 (Borges & Ferreira, 2015;Charilaos et al, 2015;Jacoby & Monteiro, 2014). No presente estudo encontrou-se Alpha de Cronbach de 0,90, patamar que vem a corroborar a sua excelente confiabilidade interna para investigar o AM no trabalho.…”
Section: Instrumentosunclassified